Penyuluhan Pembuatan Desain Packaging dan Digitalisasi Sosial Media kepada Pengrajin Manik-Manik di Lembang Angin-Angin - Gabryella Ivanka Rerungan; Claudio Claudio; Emilio Juan Pablo; Efraim Kevin; Etha Sandarinding; Isak Pasulu (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
The work program for creating logo and packaging designs as well as digital technology is a service to the community engaged in the production business of bead craftsmen in Lembang Angin- Angin. These bead craftsmen have been established in Lembang Angin-angin for a long time, but their marketing methods are still very minimal and there is a lack of community skills related to UMKM. Therefore, these UMKM need to be given counseling about the importance of branding and the use of digital marketing so that their marketing system can be better so that they can expand the target market coverage and support marketing activities through business accounts on digital media. The method used is by providing counseling in the form of making a logo. , packaging and training on how to manage digital media for selling beads. This program has the potential to increase the sales appeal of beaded products, as well as serve as a symbol of product identity to make it easier for consumers to remember the product. This will support increased marketing activities and increase sales of the bead business.